Delineating circulating lymphocyte subsets in the transition from gout remission to recurrence - Yu, Hanjie; Wang, Ling; Qin, Ling; Yu, Hanqing; Hu, Ran; Jia, Zhenghu; Bao, Hui; Wang, Haichao; Xue, Wen; Song, Yaxiang; Yin, Zhinan; Peng, Ai (Frontiers in Immunology, 2025)
ObjectivesLymphocytes and their subsets are implicated in both the onset and remission of gout. However, the specific roles in gout recurrence and complete remission remain unclear. This study aimed to characterize lymphocyte immunophenotypes across different stages of gout and developed a predictive model for remission and recurrence of gout.MethodsPlasma levels of 75 lymphocyte immunophenotypes were determined using multiplex flow cytometry in patients with acute gout flare (AG, n=78), gout remission (RG, n=63), and healthy controls (NC, n=66). Lymphocyte immunophenotyping candidates and significant clinical parameters were subjected to LASSO regression for conducting a predictive model.ResultsSignificant variations in lymphocyte profiles were identified among the groups. A combination of T peripheral helper cells, virus-specific cytotoxic natural killer (NK) cells, inhibition of Vδ1 and Vδ2 cells, along with BMI, eGFR, hemoglobin, uric acid, distinguished RG from NC (AUC=0.934). Similarly, inhibition of Vδ2 cells, virus-specific cytotoxic NK cells, inactive and terminally differentiated virus-specific CD8+ T cells, plus hematological parameters, classified RG from AG (AUC = 0.814) and predicted gout recurrence in a one-year follow-up validation cohort (AUC = 0.724). Inhibition of Vδ2 cells and virus-infected specific cytotoxic NK cells are strongly associated with gout recurrence and complete remission.ConclusionSignificant alterations in lymphocyte immunophenotypes, notably the inhibition of Vδ2 cells and virus-infected specific cytotoxic NK cells during the transition from gout recurrence to complete remission, provide compelling evidence to enhance the clinical delineation of gout stages and propel mechanistic investigations into the progression of gout.